Regenerated graphite composite negative electrode material, preparation method thereof and secondary battery
By performing strong alkali solution pore formation and silane gas deposition treatment on waste graphite, and mixing it with binder and conductive agent to granulate, the problem of insufficient capacity, cycle stability and fast charging performance of waste graphite negative electrode materials is solved, and the problem of insufficient capacity, cycle stability and fast charging performance of waste graphite negative electrode materials is achieved. Recycled graphite composite anode material with high capacity, stability and fast charging performance.
Patent Information
- Application Number
- CN202411647693.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to effectively improve the capacity, cycle stability and fast charging performance of waste graphite negative electrode materials, and the recycled graphite has many surface defects, poor high-temperature performance, and low g capacity.
By placing waste graphite in a strong alkali solution for pore formation, porous regenerated graphite is formed, and then silane gas is deposited under an inert atmosphere to form a composite material, and mixed with binder and conductive agent to granulate, and then regenerate after post-treatment Graphite composite anode material.
It improves the gram capacity and cycle stability of recycled graphite materials, enhances fast charging performance, and makes the material structure more stable, reducing the side reactions and volume expansion of solid-state deposition silicon.
Smart Images

Figure CN119495727A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a recycled graphite composite negative electrode material, a preparation method thereof, and a secondary battery. Background Art
[0002] As the global demand for new energy sources grows, lithium-ion batteries are widely used in electric vehicles, energy storage systems and other fields due to their high energy density, long cycle life and environmental protection. According to statistics, the global output of negative electrode materials in 2023 is about 1.76 million tons, of which China's negative electrode material shipments are about 1.68 million tons, accounting for more than 95%. With such a high market share, negative electrode material recycling technology has gradually attracted people's attention.
[0003] The waste graphite negative electrode material extracted from the discarded lithium-ion battery contains a large amount of impurities, such as binders, conductive agents, electrolytes and a small amount of metals. Direct use will cause the battery cycle performance to deteriorate rapidly, and further purification and modification are required. For example: Chinese patent (CN118183729A) introduces a method for regenerating waste graphite negative electrode materials, which is to subject the waste graphite to high-temperature heat treatment in a halogen-containing atmosphere, solidify and modify the surface of the waste graphite, and then micro-oxidize it at a lower temperature, and then quench the micro-oxidized graphite and then carbon-coat it to obtain regenerated graphite with excellent low-temperature performance. The capacity retention rate of the regenerated graphite at -40°C can reach 95.6% of that at room temperature, but the regenerated graphite has many surface defects, and the high-temperature performance is expected to be poor, and the regenerated graphite obtained has a low specific capacity.
[0004] Industry researchers have also proposed many simple and efficient methods for regenerating waste graphite, such as microwave heating and Joule heating. However, the regenerated graphite surfaces produced by these methods are anisotropic, which is not conducive to the rapid embedding of lithium ions and has poor fast charging performance. In addition, they cannot solve the problem of low gram capacity of regenerated graphite. Summary of the invention
[0005] The present application provides a recycled graphite composite negative electrode material, a preparation method thereof and a secondary battery, which can prepare a recycled graphite composite negative electrode material with high gram capacity, cycle stability and fast charging performance.
[0006] Specifically, the present application is implemented through the following technical solutions:
[0007] On the one hand, the present application provides a method for preparing a regenerated graphite composite negative electrode material, comprising:
[0008] The waste graphite is placed in a strong alkaline solution for pore formation to obtain porous regenerated graphite;
[0009] Under an inert atmosphere, depositing silane gas on the surface and pores of the porous regenerated graphite to obtain a composite material;
[0010] The composite material, the binder and the conductive agent are mixed and granulated, and then post-processed to obtain a regenerated graphite composite negative electrode material.
[0011] Optionally, the concentration of the strong alkali solution is 1 to 3 mol / L, and the strong alkali solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution and a barium hydroxide solution.
[0012] Optionally, the temperature of the pore-making treatment is 24-26° C., and the time of the pore-making treatment is 1-4 hours.
[0013] Optionally, the deposition method of the silane gas includes chemical vapor deposition, the temperature of the chemical vapor deposition is 400-600° C., the time of the chemical vapor deposition is 1-4 hours, and the heating rate of the chemical vapor deposition is 5-10° C. / min;
[0014] And / or, the temperature of the mixing and granulating is 240-260° C., and the time of the mixing and granulating is 1-3 hours.
[0015] Optionally, the binder includes a carbon-containing binder, and the mass ratio of the composite material to the carbon-containing binder is (2-10):1;
[0016] And / or, the mass ratio of the composite material to the conductive agent is (20-100):1.
[0017] Optionally, the volume median particle size of the waste graphite is 1 to 4 μm;
[0018] And / or, the conductive agent includes at least one of carbon nanotubes, graphene and acetylene black;
[0019] And / or, the binder includes a carbonaceous binder, and the carbonaceous binder includes at least one of petroleum asphalt, coal tar pitch, phenolic resin and epoxy resin;
[0020] And / or, the silane gas includes at least one of monosilane and disilane;
[0021] And / or, the inert atmosphere includes at least one of nitrogen and argon.
[0022] Optionally, the post-treatment includes a high-temperature insulation treatment, the temperature of the high-temperature insulation treatment is 800-1000°C, the time of the high-temperature insulation treatment is 1-3h, and the heating rate of the high-temperature insulation treatment is 5-10°C / min.
[0023] Optionally, the post-treatment further comprises cooling after the high-temperature heat preservation treatment, and performing a crushing treatment after cooling; the volume median particle size of the regenerated graphite composite negative electrode material obtained after the crushing is 7 to 15 μm.
[0024] On the other hand, the present application also provides a regenerated graphite composite negative electrode material, which is prepared by any of the above-mentioned methods for preparing the regenerated graphite composite negative electrode material.
[0025] In another aspect, the present application provides a secondary battery, comprising a battery negative electrode, wherein the battery negative electrode comprises the recycled graphite composite negative electrode material as described above.
[0026] The technical solution provided by this application can achieve the following beneficial effects:
[0027] The present application provides a regenerated graphite composite negative electrode material and a preparation method thereof and a secondary battery. First, a strong alkaline solution is used to perform surface pore formation on waste graphite to obtain porous regenerated graphite, which is convenient for providing a more sufficient specific surface area for the solid deposited silicon formed by subsequent high-temperature cracking of silane gas, and at the same time, impurities such as metal oxides attached to the surface of the waste graphite can be removed in the process of pore formation. Then, the silane gas is uniformly deposited on the outer surface of the porous regenerated graphite and the inner surface in the pores, so that the outer surface of the porous regenerated graphite and the inner surface in the pores are uniformly attached with a large amount of solid deposited silicon, which not only effectively increases the gram capacity of the regenerated graphite material, but also the solid deposited silicon located in the pores can reduce the infiltration contact with the electrolyte, effectively alleviate the side reaction of the solid deposited silicon and the volume expansion, make the structure more stable, and not easily fail due to its own volume change during the battery cycle. Finally, the porous regenerated graphite with solid-state deposited silicon attached, i.e., the composite material, is mixed with a binder and a conductive agent for granulation, which can form a uniform coating layer on the surface of the material, exhibiting isotropy and providing more abundant lithium insertion sites, so that the prepared regenerated graphite composite negative electrode material has a higher gram capacity, cycle stability and fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a flow chart of a method for preparing a regenerated graphite composite negative electrode material shown in an exemplary embodiment of the present application.
[0029] Figure 2 It is a schematic structural diagram of a regenerated graphite composite negative electrode material shown in an exemplary embodiment of the present application.
[0030] Figure numerals: 1. porous regenerated graphite; 2. solid-state deposited silicon; 3. conductive agent; 4. amorphous carbon. DETAILED DESCRIPTION
[0031] The technical solution of the present application will be described in detail below in conjunction with the accompanying drawings.
[0032] Here, the technical solutions in the embodiments (or "implementations") of the present application will be described clearly and completely in conjunction with the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements.
[0033] If there are terms involving directional indications or positional relationships in the embodiments of the present application (such as up, down, left, right, front, back, inside, outside, top, bottom, center, vertical, horizontal, longitudinal, transverse, length, width, counterclockwise, clockwise, axial, radial, circumferential, etc.), such terms are only used to explain the relative positional relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings); if the specific posture changes, the directional indication or positional relationship will also change accordingly. In addition, the terms "first", "second", etc. involved in the embodiments of the present application are only used for the purpose of convenience of description and cannot be understood as indicating or implying relative importance.
[0034] See also Figure 1 The present application provides a method for preparing a regenerated graphite composite negative electrode material, comprising:
[0035] S1: placing waste graphite in a strong alkaline solution for pore formation to obtain porous regenerated graphite;
[0036] S2: Under an inert atmosphere, silane gas is deposited on the surface and pores of porous regenerated graphite to obtain a composite material;
[0037] S3: After the composite material, the binder and the conductive agent are mixed and granulated, a regenerated graphite composite negative electrode material is obtained through post-processing.
[0038] Because waste graphite has undergone multiple lithium insertion and extraction processes before being discarded, the internal structure of the graphite has been damaged to a certain extent. Although the damaged crystal structure inside the graphite can be repaired to a certain extent by using traditional heat treatment methods, the degree of repair is limited, and the problem of poor cycle stability is still prone to occur during subsequent battery performance tests. In addition, the recycled graphite formed by traditional heat treatment of waste graphite has a low specific capacity, and the surface of the recycled graphite is similar to that of fresh graphite, which is an anisotropic structure with fewer active sites for lithium ion embedding, higher charge transfer impedance, and poor fast charging performance.
[0039] The above-mentioned preparation method provided by the present application first uses a strong alkaline solution to make pores on the surface of waste graphite to obtain porous regenerated graphite, which is convenient for providing a more sufficient specific surface area for the solid deposited silicon formed by the subsequent high-temperature cracking of silane gas, and at the same time, impurities such as metal oxides attached to the surface of the waste graphite can be removed in the process of making pores. Then the silane gas is evenly deposited on the outer surface of the porous regenerated graphite and the inner surface in the pores, so that the outer surface of the porous regenerated graphite and the inner surface in the pores are evenly attached with a large amount of solid deposited silicon, which not only effectively increases the gram capacity of the regenerated graphite material, but also the solid deposited silicon located in the pores can reduce the infiltration contact with the electrolyte, effectively alleviate the side reactions and volume expansion of the solid deposited silicon, make the structure more stable, and not easily fail due to its own volume change during the battery cycle. Finally, the porous regenerated graphite with solid-state deposited silicon attached, i.e., the composite material, is mixed with a binder and a conductive agent for granulation, which can form a uniform coating layer on the surface of the material, exhibiting isotropy and providing more abundant lithium insertion sites, so that the prepared regenerated graphite composite negative electrode material has a higher gram capacity, cycle stability and fast charging performance.
[0040] It should be noted that the above-mentioned strong alkaline solution is an alkaline solution with a pH of 14.
[0041] In one embodiment, the concentration of the strong alkali solution is 1 to 3 mol / L, and the strong alkali solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, and a barium hydroxide solution. Thus, porous regenerated graphite with a relatively good porosity can be prepared, avoiding the corrosion of the graphite by a high concentration of strong alkali, which causes the graphite to be partially dissolved and causes structural damage, and also avoiding the insignificant pore-forming effect caused by a lower concentration of strong alkali.
[0042] In one embodiment, the temperature of the pore-forming treatment is 24-26° C., and the time of the pore-forming treatment is 1-4 hours.
[0043] In one embodiment, the deposition method of silane gas includes chemical vapor deposition, the temperature of chemical vapor deposition is 400-600° C., the time of chemical vapor deposition is 1-4 hours, and the heating rate of chemical vapor deposition is 5-10° C. / min. Thus, the silane gas can be evenly dispersed, which is conducive to the solid-state deposited silicon being more evenly attached to each pore, so as to further reduce the volume expansion of the regenerated graphite composite negative electrode material during the lithium insertion process.
[0044] In one embodiment, the temperature of the mixed granulation is 240-260° C., and the time of the mixed granulation is 1-3 hours. Thus, during the lithium insertion process, the expansion stress generated by the solid-state deposited silicon can be doubly buffered at the pore wall and the amorphous carbon layer, further suppressing the volume expansion of the recycled graphite composite negative electrode material, and making the structure more stable.
[0045] In one embodiment, the binder includes a carbon-containing binder, and the mass ratio of the composite material to the carbon-containing binder is (2 to 10): 1. Thus, by mixing and granulating the porous regenerated graphite with solid-state deposited silicon attached, that is, the composite material, and the carbon-containing binder according to the above conditions, a composite particle structure with a high degree of compositeness coated with amorphous carbon on the surface can be formed, so that the prepared regenerated graphite composite negative electrode material has an overall macroscopic appearance of isotropy, a low crystal plane orientation, and abundant lithium insertion sites, which is conducive to the rapid embedding of lithium ions into the particles from all directions, so that the charge transfer impedance is low, the fast charging performance is better, and the excessive amorphous carbon component is avoided to affect the cycle performance.
[0046] In one embodiment, the mass ratio of the composite material to the conductive agent is (20-100): 1. Thus, under the premise of a stable composite particle structure, the regenerated graphite composite negative electrode material can be ensured to have a faster electron transfer rate and a lower ohmic impedance, so as to further improve the fast charging performance.
[0047] In one embodiment, the volume median particle size of the waste graphite is 1 to 4 μm. In one embodiment, the conductive agent includes at least one of carbon nanotubes, graphene and acetylene black. In one embodiment, the binder includes a carbonaceous binder, and the carbonaceous binder includes at least one of petroleum asphalt, coal tar pitch, phenolic resin and epoxy resin. In one embodiment, the silane gas includes at least one of monosilane and disilane. In one embodiment, the inert atmosphere includes at least one of nitrogen and argon.
[0048] In one embodiment, the post-treatment includes a high temperature insulation treatment, the temperature of the high temperature insulation treatment is 800-1000° C., the time of the high temperature insulation treatment is 1-3 hours, and the heating rate of the high temperature insulation treatment is 5-10° C. / min.
[0049] In one embodiment, the post-treatment further includes cooling after the high-temperature insulation treatment, and performing a crushing treatment after cooling; the volume median particle size of the regenerated graphite composite negative electrode material obtained after the crushing is 7 to 15 μm.
[0050] like Figure 2 As shown, the present application provides a regenerated graphite composite negative electrode material, which is prepared by any of the above-mentioned methods for preparing the regenerated graphite composite negative electrode material.
[0051] The regenerated graphite composite negative electrode material prepared in the present application can be deposited on the outer surface of the porous regenerated graphite 1 and the inner surface of the pores to form solid deposited silicon 2, and then combined with a conductive agent 3 and a coating layer of amorphous carbon 4 attached to the surface, which can improve the gram capacity, cycle stability and fast charging performance.
[0052] The present application also provides a secondary battery, including a battery negative electrode, wherein the battery negative electrode includes the above-mentioned recycled graphite composite negative electrode material. Exemplarily, the secondary battery includes but is not limited to a lithium-ion battery.
[0053] Example 1
[0054] 1. Preparation of recycled graphite composite negative electrode materials:
[0055] (1) placing waste graphite with a volume median particle size of 3 μm in a 2 mol / L KOH solution and soaking it for 2 h to perform pore-forming treatment, filtering out the precipitate after the pore-forming treatment, and rinsing it with ultrapure water for 10 min to obtain porous regenerated graphite;
[0056] (2) placing the porous regenerated graphite in a CVD tubular atmosphere furnace and passing argon gas for 1 hour to form an oxygen-free environment inside the tubular furnace. Subsequently, the tubular furnace was heated to 450°C at a rate of 5°C / min, and monosilane gas was passed at a rate of 2L / min for 1.5 hours to deposit the silane gas on the surface and pores of the porous regenerated graphite, and then naturally cooled to room temperature to obtain a composite material;
[0057] (3) The composite material, coal tar pitch and single-walled carbon nanotubes were added into a horizontal granulation kettle at 250°C in a mass ratio of 10:2:0.3 for low-temperature granulation. The mixture was then transferred into a tubular furnace in an argon atmosphere and heated to 1000°C at a rate of 5°C / min and kept at that temperature for 2 h. After natural cooling, the material was broken into pieces of 11 μm to obtain an isotropic regenerated graphite composite negative electrode material.
[0058] 2. Preparation of negative electrode sheet
[0059] (1) The mass ratio of the regenerated graphite composite negative electrode material, conductive carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in the negative electrode slurry is 93:3:2:2, and the solid content is 50%. The regenerated graphite composite negative electrode material is prepared by the above-mentioned preparation method of the regenerated graphite composite negative electrode material.
[0060] (2) The preparation method of the negative electrode slurry is as follows: add solvent deionized water, conductive carbon black and 70% sodium carboxymethyl cellulose (CMC) powder to a stirring tank, stir at a low speed for 2 hours to form a conductive glue solution; add regenerated graphite composite negative electrode material to the conductive glue solution, stir at a high speed of 1500r / min for 1 hour to form a first mixed solution. Add styrene-butadiene rubber (SBR) to the first mixed solution, stir at a high speed of 1000r / min for 1 hour to form a second mixed solution. Add ethanol and the remaining 30% sodium carboxymethyl cellulose (CMC) powder to the second mixed solution, stir at a high speed of 1000r / min for 2 hours to prepare a negative electrode slurry. The mass ratio of deionized water to ethanol in the slurry is 9:1. The negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, dried in an oven, and cold pressed and cut into pieces to obtain a negative electrode sheet.
[0061] 3. Preparation of positive electrode sheet
[0062] The positive electrode active material NCM523, the conductive agent carbon nanotubes, and the binder PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 93:3:4, and the solvent NMP (N-methylpyrrolidone) is added, and the mixture is stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, dried in an oven, and then cold pressed and cut to obtain a positive electrode sheet.
[0063] 4. Preparation of electrolyte
[0064] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then 1 mol / L concentration of fully dried lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte.
[0065] 5. Preparation of lithium-ion batteries
[0066] The positive electrode sheet, isolation film (polyethylene film), and negative electrode sheet are stacked in sequence, with the isolation film being placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0067] Example 2
[0068] The difference from Example 1 is that in the preparation process of the recycled graphite composite negative electrode material, the volume median particle size of the waste graphite is replaced with 1.2 μm. The other experimental conditions are exactly the same as those in Example 1.
[0069] Example 3
[0070] The difference from Example 1 is that in the preparation process of the recycled graphite composite negative electrode material, the volume median particle size of the waste graphite is replaced with 2 μm. The other experimental conditions are exactly the same as those in Example 1.
[0071] Example 4
[0072] The difference from Example 1 is that in the preparation process of the recycled graphite composite negative electrode material, the volume median particle size of the waste graphite is replaced with 3.4 μm. The other experimental conditions are exactly the same as those in Example 1.
[0073] Example 5
[0074] The difference from Example 1 is that during the preparation of the regenerated graphite composite negative electrode material, the time for introducing monosilane gas is 1 hour. The other experimental conditions are exactly the same as those in Example 1.
[0075] Example 6
[0076] The difference from Example 1 is that during the preparation of the regenerated graphite composite negative electrode material, the time for introducing monosilane gas is 2 hours. The other experimental conditions are exactly the same as those in Example 1.
[0077] Example 7
[0078] The difference from Example 1 is that during the preparation of the regenerated graphite composite negative electrode material, the time for introducing monosilane gas is 3 hours. The other experimental conditions are exactly the same as those in Example 1.
[0079] Example 8
[0080] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, an isotropic regenerated graphite composite negative electrode material with a volume median particle size of 7 μm is obtained after crushing. The other experimental conditions are exactly the same as those in Example 1.
[0081] Example 9
[0082] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, an isotropic regenerated graphite composite negative electrode material with a volume median particle size of 9 μm is obtained after crushing. The other experimental conditions are exactly the same as those in Example 1.
[0083] Example 10
[0084] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, an isotropic regenerated graphite composite negative electrode material with a volume median particle size of 13 μm is obtained after crushing. The other experimental conditions are exactly the same as those in Example 1.
[0085] Embodiment 11
[0086] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, an isotropic regenerated graphite composite negative electrode material with a volume median particle size of 15 μm is obtained after crushing. The other experimental conditions are exactly the same as those in Example 1.
[0087] Example 12
[0088] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:3:0.3. The other experimental conditions are exactly the same as those in Example 1.
[0089] Embodiment 13
[0090] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:1:0.3. The other experimental conditions are exactly the same as those in Example 1.
[0091] Embodiment 14
[0092] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:2:0.5. The other experimental conditions are exactly the same as those in Example 1.
[0093] Embodiment 15
[0094] The difference from Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:2:0.1. The other experimental conditions are exactly the same as those in Example 1.
[0095] Comparative Example 1
[0096] 1. Preparation of recycled graphite composite negative electrode materials:
[0097] (1) placing waste graphite with a volume median particle size of 7 μm in a 2 mol / L KOH solution and soaking it for 2 h to perform pore-forming treatment, filtering out the precipitate after the pore-forming treatment, and rinsing it with ultrapure water for 10 min to obtain porous regenerated graphite;
[0098] (2) placing the porous regenerated graphite in a CVD tubular atmosphere furnace and passing argon gas for 1 hour to form an oxygen-free environment inside the tubular furnace. Subsequently, the tubular furnace was heated to 450°C at a rate of 5°C / min, and monosilane gas was passed at a rate of 2L / min for 1.5 hours to deposit the silane gas on the surface and pores of the porous regenerated graphite, and then naturally cooled to room temperature to obtain a composite material;
[0099] (3) The composite material, coal tar pitch and single-walled carbon nanotubes were added into a horizontal granulation kettle at 250°C in a mass ratio of 10:2:0.3 for low-temperature granulation. The mixture was then transferred into a tubular furnace in an argon atmosphere and heated to 1000°C at a rate of 5°C / min and kept at that temperature for 2 h. After natural cooling, the material was broken into pieces of 11 μm to obtain an isotropic regenerated graphite composite negative electrode material.
[0100] 2. Preparation of negative electrode sheet
[0101] (1) The mass ratio of the regenerated graphite composite negative electrode material, conductive carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in the negative electrode slurry is 93:3:2:2, and the solid content is 50%. The regenerated graphite composite negative electrode material is prepared by the above-mentioned preparation method of the regenerated graphite composite negative electrode material.
[0102] (2) The preparation method of the negative electrode slurry is as follows: add solvent deionized water, conductive carbon black and 70% sodium carboxymethyl cellulose (CMC) powder to a stirring tank, stir at a low speed for 2 hours to form a conductive glue solution; add regenerated graphite composite negative electrode material to the conductive glue solution, stir at a high speed of 1500r / min for 1 hour to form a first mixed solution. Add styrene-butadiene rubber (SBR) to the first mixed solution, stir at a high speed of 1000r / min for 1 hour to form a second mixed solution. Add ethanol and the remaining 30% sodium carboxymethyl cellulose (CMC) powder to the second mixed solution, stir at a high speed of 1000r / min for 2 hours to prepare a negative electrode slurry. The mass ratio of deionized water to ethanol in the slurry is 9:1. The negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, dried in an oven, and cold pressed and cut into pieces to obtain a negative electrode sheet.
[0103] 3. Preparation of positive electrode sheet
[0104] The positive electrode active material NCM523, the conductive agent carbon nanotubes, and the binder PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 93:3:4, and the solvent NMP (N-methylpyrrolidone) is added, and the mixture is stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, dried in an oven, and then cold pressed and cut to obtain a positive electrode sheet.
[0105] 4. Preparation of electrolyte
[0106] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then 1 mol / L concentration of fully dried lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte.
[0107] 5. Preparation of lithium-ion batteries
[0108] The positive electrode sheet, isolation film (polyethylene film), and negative electrode sheet are stacked in sequence, with the isolation film being placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0109] Comparative Example 2
[0110] The difference from Comparative Example 1 is that in the preparation process of the recycled graphite composite negative electrode material, the waste graphite with a volume median particle size of 0.6 μm is immersed in a 2 mol / L KOH solution. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0111] Comparative Example 3
[0112] The difference from Comparative Example 1 is that during the preparation of the regenerated graphite composite negative electrode material, the time for introducing monosilane gas is 6 hours. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0113] Comparative Example 4
[0114] The difference from Comparative Example 1 is that during the preparation of the regenerated graphite composite negative electrode material, the time for introducing monosilane gas is 0.5 h. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0115] Comparative Example 5
[0116] The difference from Comparative Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, an isotropic regenerated graphite composite negative electrode material with a volume median particle size of 16 μm is obtained after crushing. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0117] Comparative Example 6
[0118] The difference from Comparative Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, an isotropic regenerated graphite composite negative electrode material with a volume median particle size of 6 μm is obtained after crushing. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0119] Comparative Example 7
[0120] The difference from Comparative Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:4:0.3. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0121] Comparative Example 8
[0122] The difference from Comparative Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:0.5:0.3. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0123] Comparative Example 9
[0124] The difference from Comparative Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:2:1. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0125] Comparative Example 10
[0126] The difference from Comparative Example 1 is that in the preparation process of the regenerated graphite composite negative electrode material, the mass ratio of the composite material, coal tar pitch and single-walled carbon nanotube is 10:2:0.05. The other experimental conditions are exactly the same as those of Comparative Example 1.
[0127] Test Example 1
[0128] The regenerated graphite composite negative electrode materials prepared in the above Examples 1 to 15 and Comparative Examples 1 to 10 were subjected to the following structural parameter tests:
[0129] (1) Gram capacity test of recycled graphite composite negative electrode material: After the negative electrode sheet is prepared with recycled graphite composite negative electrode material as the negative electrode active material, it is assembled into a button battery together with a lithium sheet, and then the charging capacity is tested using a blue power tester (CT2001A).
[0130] (2) Volume median particle size test of waste graphite and recycled graphite composite negative electrode materials: obtained by using a laser diffraction particle size analyzer (MS2000). The sample particles are dispersed in a liquid medium at a concentration of 200-300 mg / L, and a monochromatic light beam is passed through. After the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values of the relevant scattering diagram at many angles and records these values for analysis. Using the Rayleigh scattering formula, the scattering values are calculated to obtain the ratio of the volume of particles of each particle size level to the total volume, thereby obtaining the volume distribution of the particle size.
[0131] Test Example 2
[0132] The lithium ion batteries prepared in the above Examples 1 to 15 and Comparative Examples 1 to 10 were subjected to the following performance tests:
[0133] (1) Dynamic performance test: At 25°C, the lithium-ion battery was fully charged at a rate of 4C and fully discharged at a rate of 1C for 10 times, and then the lithium-ion battery was fully charged at a rate of 4C, and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, the area of lithium deposition on the surface of the negative electrode is less than 5%, which is considered to be slight lithium deposition, the area of lithium deposition on the surface of the negative electrode is 5% to 40%, which is considered to be moderate lithium deposition, and the area of lithium deposition on the surface of the negative electrode is greater than 40%, which is considered to be severe lithium deposition.
[0134] (2) Cycle performance test: At 25° C., the lithium secondary battery was charged at a 2C rate and discharged at a 1C rate to perform a full charge and discharge cycle test until the capacity of the lithium secondary battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0135] The above Examples 1 to 15 and Comparative Examples 1 to 10 were tested according to the above Test Example 1 and Test Example 2, respectively. The test results are shown in Table 1.
[0136] Table 1
[0137]
[0138] Waste graphite is the main part of the regenerated graphite composite negative electrode material of this application, and the particle size cannot be too large or too small. When the particle size of the waste graphite is too large, the granulation degree of the regenerated graphite composite negative electrode material is low, the graphite crystal orientation degree in the material is high, and the isotropy degree of the material is reduced, which is not conducive to rapid lithium extraction. Comparative Example 1 uses waste graphite with too large a particle size, and the final kinetic performance test result is severe lithium precipitation. When the particle size of the waste graphite is too small, the particle structure of the graphite is severely damaged, and too many end faces are exposed. It is easy to react with the electrolyte during a long cycle, resulting in a large amount of active lithium loss. Comparative Example 2 uses waste graphite with too small a particle size, and the final test cycle number is only 1563.
[0139] The silane gas deposition time has a direct impact on the capacity and cycle performance of the regenerated graphite composite negative electrode material. When the silane gas deposition time is too short, the capacity of the regenerated graphite composite negative electrode material is low, which is not conducive to the improvement of the battery capacity. The gram capacity of Comparative Example 4 is only 398 mAh / g. When the silane gas deposition time is too long, the silicon content in the regenerated graphite composite negative electrode material is high, the volume expansion generated during the lithium insertion process is large, the particle structure stability is poor, and the cycle performance is poor. The number of cycles of Comparative Example 3 is only 1221.
[0140] In addition, the finished particle size of the recycled graphite composite negative electrode material also directly affects its electrochemical performance. When the particle size is too large, the diffusion path of lithium ions in the material particles is too long, and the fast charging performance is poor. The kinetic performance test result of Comparative Example 5 is severe lithium precipitation. When the particle size is too small, the particles are excessively broken, the specific surface area is large, and there are more side reactions with the electrolyte during the charging and discharging process, and the cycle performance is poor. The number of cycles of Comparative Example 6 is only 1533.
[0141] Finally, the matching ratio of the porous regenerated graphite with solid-state deposited silicon, that is, the composite material, the binder and the conductive agent is also particularly critical. When the binder content is too high, the amorphous carbon component of the regenerated graphite composite negative electrode material is too much, and there are more lithium insertion active sites on the surface of the material. During the cycle, the side reactions between the material and the electrolyte increase, and the cycle performance is poor. The number of cycles of Comparative Example 7 is only 940. When the binder content is too low, the amorphous carbon component of the regenerated graphite composite negative electrode material is too little, the lithium insertion active sites on the surface of the material are less, and the fast charging performance is poor. The kinetic performance test result of Comparative Example 8 is severe lithium precipitation. When the conductive agent content is too much, the structural stability of the regenerated graphite composite negative electrode material is poor, and the cycle performance is poor. The number of cycles of Comparative Example 9 is only 1932. When the conductive agent content is too little, the ohmic impedance of the regenerated graphite composite negative electrode material is high, and the fast charging performance is poor. The kinetic performance test result of Comparative Example 10 is severe lithium precipitation.
[0142] It should be noted that the technical solutions or technical features described in the above embodiments can be combined or supplemented with each other without causing conflicts. The scope of protection of this application is not limited to the precise structures described in the above embodiments and shown in the drawings; all modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of this application should be included in the scope of protection of this application.
Claims
1. A method for preparing a regenerated graphite composite negative electrode material, characterized in that: include: The waste graphite is placed in a strong alkaline solution for pore formation to obtain porous regenerated graphite; Under an inert atmosphere, depositing silane gas on the surface and pores of the porous regenerated graphite to obtain a composite material; The composite material, the binder and the conductive agent are mixed and granulated, and then post-processed to obtain a regenerated graphite composite negative electrode material.
2. The method for preparing the regenerated graphite composite negative electrode material according to claim 1, characterized in that: The concentration of the strong alkali solution is 1-3 mol / L, and the strong alkali solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution and a barium hydroxide solution.
3. The method for preparing the regenerated graphite composite negative electrode material according to claim 2, characterized in that: The temperature of the pore-forming treatment is 24-26° C., and the time of the pore-forming treatment is 1-4 hours.
4. The method for preparing the regenerated graphite composite negative electrode material according to claim 1, characterized in that: The deposition method of the silane gas includes chemical vapor deposition, the temperature of the chemical vapor deposition is 400-600° C., the time of the chemical vapor deposition is 1-4 hours, and the heating rate of the chemical vapor deposition is 5-10° C. / min; And / or, the temperature of the mixing and granulating is 240-260° C., and the time of the mixing and granulating is 1-3 hours.
5. The method for preparing the regenerated graphite composite negative electrode material according to claim 1, characterized in that: The binder includes a carbon-containing binder, and the mass ratio of the composite material to the carbon-containing binder is (2-10):1; And / or, the mass ratio of the composite material to the conductive agent is (20-100):
1.
6. The method for preparing the regenerated graphite composite negative electrode material according to claim 1, characterized in that: The volume median particle size of the waste graphite is 1 to 4 μm; And / or, the conductive agent includes at least one of carbon nanotubes, graphene and acetylene black; And / or, the binder includes a carbonaceous binder, and the carbonaceous binder includes at least one of petroleum asphalt, coal tar pitch, phenolic resin and epoxy resin; And / or, the silane gas includes at least one of monosilane and disilane; And / or, the inert atmosphere includes at least one of nitrogen and argon.
7. The method for preparing the regenerated graphite composite negative electrode material according to any one of claims 1 to 6, characterized in that: The post-treatment includes high-temperature insulation treatment, the temperature of the high-temperature insulation treatment is 800-1000° C., the time of the high-temperature insulation treatment is 1-3 hours, and the heating rate of the high-temperature insulation treatment is 5-10° C. / min.
8. The method for preparing the regenerated graphite composite negative electrode material according to claim 7, characterized in that: The post-treatment further comprises cooling after the high-temperature heat preservation treatment, and performing a crushing treatment after cooling; the volume median particle size of the regenerated graphite composite negative electrode material obtained after the crushing is 7 to 15 μm.
9. A recycled graphite composite negative electrode material, characterized in that: The regenerated graphite composite negative electrode material is prepared by the method for preparing the regenerated graphite composite negative electrode material according to any one of claims 1 to 8.
10. A secondary battery, comprising a negative electrode, characterized in that: The battery negative electrode comprises the recycled graphite composite negative electrode material as claimed in claim 9.
Citation Information
Patent Citations
Failure graphite-based regenerated graphite material for waste batteries and preparation method and application of failure graphite-based regenerated graphite material
CN118183729A
Cited By
Regenerated graphite quick-charging material as well as preparation and application thereof
CN120878839A